Diretrizes para uso de indicadores de desempenho em empresas construtoras - Sousa, Domingos Sávio Viana de (2016)
Regarding the increasingly competitive business scene, it has been noticeable that companies have needed to speed up the adjustment process to current market competitive strategies. Civil construction has not been different. In spite of the increasingly effort in organizational business management area, among professionals and also the academic community, it has not been enough to consolidate the performance measurement practices yet. The not systematic usage of performance indicators is still, in most construction companies, uneventful. The lack of appropriate measures related to company's strategies has been observed. Thus, this paper purpose is proposing performance indicators guidelines, used in construction companies. For this, a literature review on performance measurement in the building has been carried out, allowing the best practices and performances of the remaining knowledge gaps identification. After the theoretical study, a multiple descriptive case has been scanned, in which semi-structured interviews and documents, provided by the company, were evidence sources. The interviews results have been explored through a content analysis (CA), and have been also triangulated with the company documents through document analysis. Next, a comparative study of the companies, where the main characteristics of the enterprise system measurement were determined, has been done. Then, the guidelines for performance indicators use in most construction companies have been proposed as the aim of this research, supported by secondary objectives reached. As a matter of fact, the shortcomings observed in the measurement business systems have decreased their competitiveness, since the generated information may not emphasize the real company performance gaps, as well as provide a proactive management style for Marketplace changes. Actually, a management exercise focused on controls, that do not necessarily provide better opportunities for the company, but only a response to faults occurred, has been noticed. It ends with some future work suggestion.